2022
DOI: 10.1080/00207721.2022.2056654
|View full text |Cite
|
Sign up to set email alerts
|

Predictor-based control of time-delay systems: a survey

Abstract: With the developments of wireless data communication and network technology, time-delays are widely found in nowadays' control systems, e.g. networked control systems, mobile robot systems, and multiagent systems. Predictor-based control is an effective method dealing with long time-delays because it can generally lead to a delay-free closed-loop system by introducing a prediction for future states. Recently, various predictor-based control methods have been developed for numerous control systems subject to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 250 publications
0
11
0
Order By: Relevance
“…There are many solutions for control in systems with delay [26][27][28][29][30]. One of the most common solutions is the Smith Predictor [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many solutions for control in systems with delay [26][27][28][29][30]. One of the most common solutions is the Smith Predictor [28].…”
Section: Introductionmentioning
confidence: 99%
“…There are many solutions for control in systems with delay [26][27][28][29][30]. One of the most common solutions is the Smith Predictor [28]. However, we want to solve the problem in a simplified way-to design an MISO PBC controller for the system without delay in the measurement traces and implement it in the system with delays using the prediction of the measured state variables.…”
Section: Introductionmentioning
confidence: 99%
“…For the Lyapunov-Krasovskii based robust controller design, the upper bound of the delay needs to be given in advance. 12 To avoid this constraint condition and be able to handle time-varying delays, on-line estimation of time delay is further explored. An algebraic approach to estimate delays was proposed in Reference 13.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on mobile robotics have been reported the literature. One of the most important approaches is related to prediction-based controls; an interesting survey was pre-sented in [23]. For instance, considering delayed measurements, [24,25] provides a solution for the kinematic model, and [26] uses a simplified dynamic model.…”
mentioning
confidence: 99%
“…Furthermore, because origin e wj = [0 0 0] T is the only equilibrium point, system (23) is globally asymptotically stable.…”
mentioning
confidence: 99%